Strength-Endurance: Interaction Between Force-Velocity Condition and Power Output - Rivière, Jean Romain; Peyrot, Nicolas; Cross, Matthew R.; Messonnier, Laurent A.; Samozino, Pierre (Frontiers in Physiology, 2020)
Context: Strength-endurance mainly depends on the power output, which is often expressed relative to the individual’s maximal power capability (Pmax). However, an individual can develop the same power, but in different combinations of force and velocity (force-velocity condition). Also, at matched power output, changing the force-velocity condition results in a change of the velocity-specific relative power (Pmaxv), associated with a change in the power reserve. So far, the effect of these changing conditions on strength-endurance remains unclear. Purpose: We aimed to test the effects of force-velocity condition and power output on strength-endurance. Methods: Fourteen sportsmen performed i) force- and power-velocity relationships evaluation in squat jumps and ii) strength-endurance evaluations during repeated squat jump tests in ten different force-velocity-power conditions, individualized based on the force- and power-velocity relationships. Each condition was characterized by different i) relative power (%Pmax), ii) velocity-specific relative power (%Pmaxv), and iii) ratio between force and velocity (RFv). Strength-endurance was assessed by the maximum repetitions (SJRep), and the cumulated mechanical work (Wtot) performed until exhaustion during repeated squat jump tests. Intra and inter-day reliability of SJRep were tested in one of the ten conditions. The effects of %Pmax, %Pmaxv, and RFv on SJRep and Wtot were tested via stepwise multiple linear regressions and two-way ANOVAs. Results: SJRep exhibited almost perfect intra- and inter-day reliability (ICC=0.94 and 0.93, respectively). SJRep and Wtot were influenced by %Pmaxv and RFv (R2=0.975 and 0.971; RSME=0.242 and 0.234, respectively; both p<0.001), with the effect of RFv increasing with decreasing %Pmaxv (interaction effect, p=0.03). %Pmax was not considered as a significant predictor of strength-endurance by the multiple regressions analysis. SJRep and Wtot were higher at lower %Pmaxv and in low force-high velocity conditions (i.e., lower RFv). Conclusion: Strength-endurance was almost fully dependent on the position of the exercise conditions relative to the individual force-velocity and power-velocity relationships (characterized by %Pmaxv and RFv). Thus, the standardization of the force-velocity condition and the velocity-specific relative power should not be overlooked for strength-endurance testing and training, but also when setting fatiguing protocols.